Heterogeneity in marginal returns to language training of immigrants - Matthias Giesecke; Eric Schuss (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
We estimate the effect of language training on subsequent employment and wages of immigrants under essential heterogeneity. The identifying variation is based on regional differences in language training availability that we use to instrument endogenous participation. Estimating marginal treatment effects along the distribution of observables and unobservables that drive individual participation decisions, we find that immigrants with higher gains are more likely to select into language training than immigrants with lower gains. We document up to 15% higher employment rates and 13% wage gains for immigrants with a high desire to participate but the positive returns vanish with increasing resistance to treatment. This pattern of selection on gains correlates with unobserved ability and motivation, promoting investments in education and job-specific skills that yield higher returns when complemented by language capital in the host country. – – Die Studie untersucht den Effekt von Sprachkursen auf Beschäftigung und Löhne von Immigranten. Zur Identifikation wird exogene Variation der regionalen Verfügbarkeit von Sprachkursen genutzt. Anhand dieses Instruments werden marginale Treatment-Effekte (MTE) entlang der Verteilung beobachtbarer und unbeobachtbarer Variablen geschätzt. Die Ergebnisse zeigen, dass Immigranten mit höherem Arbeitsmarkterfolg durch Sprachkursteilnahme sich wahrscheinlicher in Sprachkurse selektieren als Immigranten mit geringeren Erträgen. Immigranten mit hoher Teilnahmepräferenz weisen eine um 15% höhere Beschäftigungsquote und bis zu 13% höhere Löhne auf, allerdings verschwinden die positiven Effekte mit abnehmender Teilnahmewahrscheinlichkeit. Die Selektion nach Arbeitsmarkterfolg korreliert mit unbeobachtbaren Eigenschaften wie Motivation und Talent, die mit höheren Investitionen in Bildung und berufsspezifischen Qualifikationen einhergehen und zu einem höheren Arbeitsmarkterfolg führen, wenn sie durch Sprachkenntnisse des Gastlandes komplementiert werden.
Keywords: F22; J24; J61; J68; O15; 330; language training; heterogeneous returns; marginal treatment effects; continuous instrument